2017
DOI: 10.1186/s12884-017-1406-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with maternal mortality in Malawi: application of the three delays model

Abstract: BackgroundThe three delays model proposes that maternal mortality is associated with delays in: 1) deciding to seek care; 2) reaching the healthcare facility; and 3) receiving care. Previously, the majority of women who died were reported to have experienced type 1 and 2 delays. With increased coverage of healthcare services, we sought to explore the relative contribution of each type of delay.Method151 maternal deaths were identified during a 12-month reproductive age mortality survey (RAMOS) conducted in Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
179
3
24

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(218 citation statements)
references
References 19 publications
12
179
3
24
Order By: Relevance
“…Delay 2 factors featured prominently as contributing to more than a third of the reviewed maternal deaths in both the MDSR and EmONC assessment. This finding is confirmed by other studies from Ethiopia, Malawi and Nigeria in which Delay 2 was found to contribute to 34.7 to 59.6% of maternal deaths [16,18,25,27]. Although the EmONC data failed to include specific aspects related to Delay 2, lack of transportation was found as the main contributor for Delay 2 according to the MDSR data.…”
Section: Discussionsupporting
confidence: 82%
“…Delay 2 factors featured prominently as contributing to more than a third of the reviewed maternal deaths in both the MDSR and EmONC assessment. This finding is confirmed by other studies from Ethiopia, Malawi and Nigeria in which Delay 2 was found to contribute to 34.7 to 59.6% of maternal deaths [16,18,25,27]. Although the EmONC data failed to include specific aspects related to Delay 2, lack of transportation was found as the main contributor for Delay 2 according to the MDSR data.…”
Section: Discussionsupporting
confidence: 82%
“…Studies using the Three Delays Model have found delays in reaching and receiving care to be most common, and that appears to be true in our population as well . Patients with Medicaid insurance or who were uninsured or low income were less likely to receive chemotherapy and surgery, and this is illustrative of this point.…”
Section: Discussionsupporting
confidence: 58%
“…Our findings are in line with several other studies which identify these delays as an important cause of maternal death. 9,20 Poor utilization of health care during pregnancy in form of less than 4 ante-natal visits and home delivery are also found to be risk factors for maternal death in several studies. 21 Our study showed that the presence of anemia at the time of development of PPH raised the odds of death by five times.…”
Section: Discussionmentioning
confidence: 99%